PENGARUH PENGGUNAAN MEDIA PETA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN SEJARAH INDONESIA DI SMA CENDANA PEKANBARU - Nanda Rahmatika Syawali; Bedriati Ibrahim; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The learning process played by educators, not only the delivery of information but educators should encourage students looking for information to then build their own knowledge. Map media is one of the historical learning media that can be used to assist teachers in giving lessons to students. This research aims to find out the influence of map media use by teachers in Indonesian History subjects in grade X of SMA Cendana Pekanbaru. This research was conducted to analyze the influence of map learning media on Indonesian History subjects on the learning results of cendana pekanbaru high school students with amount of students is 26 peoples . In the statistical data of the Independent Sample T-Test there is a significant average difference between the Experiment Class which is 84.00 and control class 76.00. From the test it can be concluded that the use of Map media in historical learning is more effective when compared to chart media. From the results of Independent-Samples T Test obtained a calculated T value from the Post-test group Experiment-Control of 3,706. From that data, it looks like the value of t count 3,719> t table2.00856, the value of probability or Sig (2-tailed) 0.001< 0.05 until H1 is received and H0 is rejected. It can be concluded that the map learning media on Indonesian History subjects affects the learning results of students at SMA Cendana Pekanbaru.Key Words: Influence, Map Media, Learning Outcomes, Historical Learning